1997
DOI: 10.1159/000127223
|View full text |Cite
|
Sign up to set email alerts
|

Central Administration of the Neurotensin Receptor Antagonist, SR48692, Modulates Diurnal and Stress-Related Hypothalamic-Pituitary-Adrenal Activity

Abstract: Previous studies in our laboratory suggest that neurotensin (NT) acts centrally to modulate adrenocorticotropin hormone (ACTH) and corticosterone release. In the present studies, we examined hypothalamic-pituitary-adrenal (HPA) function under basal conditions and during restraint stress following central administration of the highly specific NT receptor antagonist, SR48692. Chronic delivery of SR48692 to the paraventricular nucleus (PVN) of the hypothalamus via indwelling central cannulae attenuated both the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 46 publications
(65 reference statements)
0
6
1
Order By: Relevance
“…In contrast, results previously obtained by our group showed that rats chronically implanted with cannulas filled with SR 48692 crystals near the paraventricular nucleus of the hypothalamus had a decreased nocturnal peak of corticosterone and ACTH, as well as a reduced release of both hormones after exposure to restraint or novelty stress Rowe et al 1997). Our results indicate that the effects of centrally administered SR 48692 on the circadian fluctuation of corticosterone levels are not observed when the same drug is administered systemically.…”
contrasting
confidence: 93%
See 1 more Smart Citation
“…In contrast, results previously obtained by our group showed that rats chronically implanted with cannulas filled with SR 48692 crystals near the paraventricular nucleus of the hypothalamus had a decreased nocturnal peak of corticosterone and ACTH, as well as a reduced release of both hormones after exposure to restraint or novelty stress Rowe et al 1997). Our results indicate that the effects of centrally administered SR 48692 on the circadian fluctuation of corticosterone levels are not observed when the same drug is administered systemically.…”
contrasting
confidence: 93%
“…Central injection of NT stimulates the release of ACTH and corticosterone (Gudelsky et al 1989;Nicot et al 1994). Moreover, chronic administration of SR 48692 at the level of the paraventricular nucleus of the hypothalamus decreases the circadian rise of ACTH and corticosterone plasma levels during the evening, as well as the increase in both hormones after exposure to stress Rowe et al 1997). …”
mentioning
confidence: 98%
“…NT has a stimulatory effect on ACTH secretion that is dependent on CRH. In contrast to AVP, NT does not have any measurable effect at the level of the pituitary; it may stimulate the HPA axis by acting on receptors located within the hypothalamus ( 39–41). ENK has been reported to have both stimulatory and inhibitory effects on ACTH and glucocorticoid secretion ( 42–47).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the NT-induced stimulation of HPA activity occurs via the well characterized NT receptor type (46,47) that has recently been cloned (53). This is further supported by NT antagonist studies, in which central administration of the NT receptor blocker, SR48692, attenuated both NT-and stress-induced increases in ACTH and B (3,26).…”
Section: Discussionmentioning
confidence: 78%
“…Furthermore, lesioning the PVN blocked the stimulatory effects of centrally administered NT on HPA activity. Recent data from our laboratory revealed that PVN implants of the newly developed NT receptor antagonist, SR 48692, (for pharmacological characterization see 25) significantly reduced basal as well as stress-induced ACTH and B levels compared to controls (26). NT is distributed within several nuclei that regulate HPA activity, including the PVN, arcuate nucleus and median eminence (1 1, 27, 28).…”
Section: Discussionmentioning
confidence: 99%